2014
DOI: 10.1186/1471-2393-14-61
|View full text |Cite
|
Sign up to set email alerts
|

Finger joint laxity, number of previous pregnancies and pregnancy induced back pain in a cohort study

Abstract: BackgroundGeneral joint hypermobility is estimated to affect about 10% of the population and is a prerequisite of heritable connective tissue disorders where fragile connective tissue is a prominent feature. Pregnancy induced back pain is common whereas about 10% of women still have disabling pain several years after childbirth. The pathogenesis of the pain condition is uncertain, although several risk factors are suggested including general joint hypermobility. In the present study, the possible association o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 34 publications
1
38
1
Order By: Relevance
“…Others have documented that first pregnancy, but not subsequent pregnancies, affects joint laxity yielding permanent changes of the foot (Segal et al, ). In addition, others have reported that increased joint laxity and number of previous pregnancies were also associated with the development of back pain (Lindgren & Kristiansson, ). Thus, further studies are warranted to examine hormonal changes of pregnancy related to joint laxity and development of joint pain.…”
Section: Discussionmentioning
confidence: 99%
“…Others have documented that first pregnancy, but not subsequent pregnancies, affects joint laxity yielding permanent changes of the foot (Segal et al, ). In addition, others have reported that increased joint laxity and number of previous pregnancies were also associated with the development of back pain (Lindgren & Kristiansson, ). Thus, further studies are warranted to examine hormonal changes of pregnancy related to joint laxity and development of joint pain.…”
Section: Discussionmentioning
confidence: 99%
“…Though maternal hormonal changes serve to facilitate the parturition process, some alterations may predispose to the pathogenesis of degenerative disc disease, back pain, osteoporosis, DISH, musculoskeletal injury, or alter the course of preexisting conditions such as rheumatoid arthritis and joint hypermobility syndrome. [Li et al 2007, Sarli et al 2005, Sabino et al 2008, Lingren et al 2014 Though adverse outcomes of maternal manual treatment (high velocity low amplitude thrusts) is reportedly of rare occurrence, [Cassidy et al 2009, Oliphant et al 2004, it is worthwhile to consider hormonal influences of the musculoskeletal system, particularly when managing peripartum back pain and planning peripheral and spinal joint manipulation in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy-related ligamentous laxity, caused by presence of the hormone Relaxin, has been reported to increase mobility of not only the pelvic joints, but peripheral joints as well (5,22,30,31). This laxity is related to alterations in foot and lower extremity alignment in pregnant women (18,32,37).…”
Section: Background and Significancementioning
confidence: 99%
“…Franklin et al (14) reported no relationship between specific postural alignment changes occuring during pregnancy, such as lumbar lordosis and anterior pelvic tilt, with low back pain. However, recent studies have shown a relationship between joint laxity and low back pain (22). Lindgren and Kristiansson (22) found that finger laxity early in pregnancy, specifically of the fourth finger, was associated with low back pain later in pregnancy and post-partum.…”
Section: Pregnancy and Painmentioning
confidence: 99%
See 1 more Smart Citation